Donor aortic dissection in a heart transplantation recipient. (26th April 2018) - Pozzi, Matteo; Hanna, Selina; Sebbag, Laurent; Obadia, Jean Francois
Abstract: Aortic dissection after orthotopic heart transplantation is a rare condition, and a limited number of reports have been published in the literature. Herein, we report a case of Type A aortic dissection 16 years after heart transplantation.